تحریکِ احمدیت کے مختلف مراحل کا تجزیاتی مطالعہ: Different Phases of Ahmadiyya Movement: Analytical Study - Dr. Sultan Sikandar; Dr.Abu Sufyan Qazi Furqan Ahmed (MEI, 2023)
A critical analysis of the evolutinag stages of Ahmadiyah movement.Ahmediyat was a British movement whose purpose was to establish an authentic justification for the existing subjection of Hindustan. The fidelity to the Britishers was their belief. To declare Jihad illigitimate, to negate the advent of Mehdi Mo’od and Messih Mo’od were the fundamentals of the new movement. The Muslims had a faith regarding the advent of Imam Mehdi (A.S) and Hazrat Esa (A.S) for the establishment of dominance of Islam in the last era. Through this movement they aimed to achieve the aforementioned objectives Mirza Ghulam Ahmad Qadyani committed an accursed effort to accomplish his objectives. His proclamation of Nabuwat created a divide in the islamic society. This divide became a social conflict among viious sects of Islam.